Level of Physical Activity and Its Relationship to Self-Perceived Physical Fitness in Peruvian Adolescents - Palacios-Cartagena, R.P. (2022)
Background: Physical activity and physical fitness play an important role in adolescence. Both are considered to be indicators of the current and future health status of young adults. The main objective of this article was to report the normative values of the Physical Activity Questionnaire for Adolescents (PAQ-A) and the International Fitness Scale (IFIS) instruments in Peruvian school adolescents. Methods: A sample of 1229 participants (622 girls and 607 boys) aged between 12 and 17 years was used. The type of study was descriptive-comparative. All measures used were obtained by means of self-administered instruments. The PAQ-A was used to assess the level of physical activity and the IFIS to assess the self-perceived physical fitness level of the adolescents. Results: It was observed that the PAQ-A questionnaire results obtained from the total sample was 2.34; significantly higher for boys (2.41) compared with girls (2.27). For the IFIS, the total score was 3.07, with boys obtaining 3.13 and girls 2.97. Conclusions: It was concluded that there was a direct relationship between the level of PA and self-perceived PF in Peruvian adolescents. Furthermore, adolescent boys were more physically active than girls and they had a better self-perceived PF with the exception of flexibility. Finally, there was a higher weight category involved at the lower level of PA.